The Effect of Fresh and Aged Garlic Extract-Enriched Diets on the Growth Performance of Broilers and the Oxidative Rancidity and Customer Acceptance of Chicken Meat - Ergin Ozturk; Emine Dogan (Turkish Journal of Agriculture: Food Science and Technology)
In renewable system, to improve growth performance and enhance the stability of broiler meat may be alternative dietary garlic and its derivatives. The effects of dietary fresh garlic extract (FGE) or aged garlic extract (AGE) supplementation on performance, serum cholesterol and meat thiobarbituric acid (TBA) values and the organoleptic traits of cooked meats were investigated using 540 one-day-old Ross 308 broilers. Treatments: negative control (NC, basal diet), positive control (E200, basal diet + 200 mg vitamin E kg-1), FGE (FGE10, basal diet + 10 ml FGE kg-1) and graded levels of AGE (AGE5, AGE10 and AGE15, basal diet + 5, 10 and 15 ml AGE kg-1, respectively). Sensory appraisal was used to establish the consumer acceptability of boiled, grilled or roasted meats. FGE10 increased weight gain compared to NC, AGE5 and AGE10, whereas FGE10, E200 and AGE decreased serum cholesterol and meat TBA levels compared to NC. The alleviating effects of FGE10, AGE5 and AGE10 were higher than that of vitamin E. All garlic extracts did not affect the colour and nutritional quality of raw meat. Overall consumer acceptance of meat increased by FGE10, while it decreased by AGE10 and AGE15 compared to NC. Sensory scores of grilled meat were higher than for boiled and roasted meats. These results indicate that FGE proved an advantage for sustainable broiler production due to improve in the growth performance and consumer acceptance of cooked meat.